2016
DOI: 10.1515/reveh-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and occupational exposure to cadmium in Iran: a systematic review

Abstract: AbstractIntroduction:Cadmium (Cd) is one of the heavy metals that have negative effects on human health. In Iran, there is no policy to regularly measure Cd in the general population. However, some studies have been performed on special groups and in different cities of Iran. This paper has reviewed these studies and human contamination levels in Iran.Method and materials:All acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that hypertension is more prevalent among Iranian men then woman and hypertension is one on leading causes on KC [ 26 ]. Cigarette smoking, as another risk factor for KC, is more prevalent in Iranian males [ 27 , 28 ]. Additionally, cadmium levels are higher among Iranian men who are living in industrial areas and have environmental and occupational exposure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hypertension is more prevalent among Iranian men then woman and hypertension is one on leading causes on KC [ 26 ]. Cigarette smoking, as another risk factor for KC, is more prevalent in Iranian males [ 27 , 28 ]. Additionally, cadmium levels are higher among Iranian men who are living in industrial areas and have environmental and occupational exposure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers think Cd increases the risk of premature delivery and causes brain damage in infants [10]. In Iran, cadmium levels were higher among industrial workers exposed to Cd, smokers and people living in industrial areas [8, 11].…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, Cd was higher among smokers and in people with environmental exposure from living in industrial areas [27]. Cadmium has been shown to effect reproductive hormone actions and associated with adverse reproductive outcomes in epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%